Labour market situation of Ukrainian migrants in Wielkopolskie Voivodeship: The skills mismatch perspective - Olena Shelest-Szumilas (International Entrepreneurship Review)
Objective: The main purpose of the present article is to analyse the situation of Ukrainian migrants in the Greater Poland (Wielkopolskie Voivodeship) labour market with a particular focus on the skills (mis)match and to identify factors contributing to it.